THE FORMULATION OF PEEL-OFF MASK FROM THE ETHANOL EXTRACT OF BILIMBI LEAVES (Averrhoa blimbi L.) AS ANTI-ACNE TREATMENT (Lantanida Journal, 2021)
This research aims to formulate and assess the efficacy of the peel-off mask as an anti-acne of ethanol extract from bilimbi leaves (Averrhoa bilimbi L.).  The method used was an experiment, evaluating the extract through the inhibition test of Staphylococcus epidermis bacteria with the paper disk diffusion method. The peel-off mask formulation added the extract with a concentration of 7% (F1), 9% (F2), 11% (F3), and without using extract (F0). The Peel-off mask preparation testing includes the detection of scents, colours, irritation checks, and the determination of peel-off anti-acne mask efficacy. This study was carried out at Akafarma of Banda Aceh and the Chemistry laboratory of FKIP Unsyiah. The findings of the inhibition zone for Staphylococcus epidermis bacteria at extract concentrations of 100%, 75%, 50% and 25% were 15 mm, 12 mm, 11 mm and 10 mm, respectively. The four peel-off mask formulas were gel, homogeneous, brown, with the distinctive scent of bilimbi leaves, and did not irritate the volunteers’ skin. The average decline in acne before and after using the mask for any formula (F0, FI, FII, and FIII) was 19.64%, 22.63%, 28.75% and 50%, respectively. The peel-off mask of ethanol extract of bilimbi leaves (Averrhoa bilimbi L.) is effective as an anti-acne treatment.
Keywords: ethanol extract; bilimbi leaves; peel-off mask; anti-acne agent